The Reindeer Botanist Alf Erling Porsild, 1901-1977 - Dathan, Wendy (Northern Lights, 2012)
This well-researched book is the first biography of one of Canada's most remarkable botanists. Alf Erling Porsild (1901-1977) grew up on the Arctic Station in West Greenland and later served as curator of botany at the National Museum of Canada. He collected thousands of specimens, greatly enlarging the National Herbarium and making it a superb research centre. For nearly twenty years, Porsild studied reindeer activities in Alaska and the Northwest Territories as part of the Reindeer Project designed to encourage grazing animal husbandry among aboriginal peoples. He published extensively, and his meticulous research and observations have particular relevance today with the growing concern over global warming in the Arctic.